Tissue Remodelling following Resection of Porcine Liver. (9th July 2015) - Nygård, Ingvild Engdal; Mortensen, Kim Erlend; Hedegaard, Jakob; Conley, Lene Nagstrup; Bendixen, Christian; Sveinbjørnsson, Baldur; Revhaug, Arthur
Abstract : Aim. To study genes regulating the extracellular matrix (ECM) and investigate the tissue remodelling following liver resection in porcine. Methods. Four pigs with 60% partial hepatectomy- (PHx-) induced liver regeneration were studied over six weeks. Four pigs underwent sham surgery and another four pigs were used as controls of the normal liver growth. Liver biopsies were taken upon laparotomy, after three and six weeks. Gene expression profiles were obtained using porcine-specific oligonucleotide microarrays. Immunohistochemical staining was performed and a proliferative index was assessed. Results. More differentially expressed genes were associated with the regulation of ECM in the resection group compared to the sham and control groups. Secreted protein acidic and rich in cysteine (SPARC) and collagen 1, alpha 2 (COL1A2) were both upregulated in the early phase of liver regeneration, validated by immunopositive cells during the remodelling phase of liver regeneration. A broadened connective tissue was demonstrated by Masson's Trichrome staining, and an immunohistochemical staining against pan-Cytokeratin (pan-CK) demonstrated a distinct pattern of migrating cells, followed by proliferating cell nuclear antigen (PCNA) positive nuclei. Conclusions. The present study demonstrates both a distinct pattern of PCNA positive nuclei and a deposition of ECM proteins in the remodelling phase of liver regeneration.